the THE EFFECT OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) OF TOLITOLI REGENCY: THE EFFECT OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) OF TOLITOLI REGENCY - Sabran (LPPM STIE Mujahidin, 2024)
The research was conducted to determine the Influence of Work Discipline on Employee Performance at the Regional Disaster Management Agency (BPBD) of Tolitoli Regency. The type of research uses quantitative descriptive, with the sample determination technique used Nonprobality Sampling (saturated sample). The data collection method uses observation, interviews, questionnaires, and documentation. The analysis method used is a simple linear regression test. From the results of the study, it was concluded that the results of the Work Discipline hypothesis test had a significant influence on Employee Performance at the Regional Disaster Management Agency (BPBD) of Tolitoli Regency. This means that the better the Work Discipline for Employee Performance at the Regional Disaster Management Agency (BPBD) of Tolitoli Regency, the better the Employee Performance will be. This is proven by a calculation of 17,114 > a table of 2,048 and a significant value of 0.000 < 0.005. So the hypothesis states